Quantifying relative afferent pupillary defects using a Sbisa bar. Issue 9 (1st September 2002) - McCormick, A; Bhola, R; Brown, L; Squirrel, D; Giles, J; Pepper, I
Abstract : Aim: To compare the Sbisa bar (Bagolini filter bar) with neutral density filters (NDF) in quantifying relative afferent pupillary defects (RAPD). Methods: 11 patients with a RAPD were graded and a neutral density filter bar was used to quantify the RAPD. This was repeated using the Sbisa bar. The Sbisa bar (Bagolini filter bar) is used by orthoptists to quantify density of suppression in amblyopia and is of a similar construct to NDFs. Before this clinical part of the study the luminance for each filter was measured, which enabled a direct comparison to be made. Results: In the analysis of patients with RAPD a high correlation was found when comparing the Sbisa and NDF bars r = 0.95. This was statistically significant (p = <0.001). Correlation was also high when the luminance values for the filters were substituted for the clinical readings ( r = 0.92; p=<0.001). Conclusion: The Sbisa bar is a comparable instrument to the NDF bar in measuring RAPD. Its availability in the clinical situation makes it a practical choice.